2019
DOI: 10.1590/0034-7167-2018-0978
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal care satisfaction: perception of caregivers with diabetes mellitus

Abstract: Objective: to understand the satisfaction of pregnant women with diabetes who took insulin during pregnancy and prenatal care performed through outpatient and inpatient follow-up. Method: a qualitative approach with analysis of 30 pregnant women who underwent prenatal care and participated in a clinical trial study carried out by the research The data were collected through interviews and analyzed from content analysis. Results: from the category Satisfaction, the following subcategories emerged: facilities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
2
0
5
Order By: Relevance
“…Twenty studies ( n = 20, 35%) included findings and discussion about women’s experiences of monitoring and of those it was seen as being negative ( n = 14, n = 70%), both positive and negative ( n = 5, 25%) and positive ( n = 1, n = 5%). In the one study that reported positive experiences only, a participant reported that she thought it was good “they are monitoring us all the time” [ 30 ]. Studies reporting negative experiences with monitoring had participants citing reasons such as feeling over-scrutinised [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty studies ( n = 20, 35%) included findings and discussion about women’s experiences of monitoring and of those it was seen as being negative ( n = 14, n = 70%), both positive and negative ( n = 5, 25%) and positive ( n = 1, n = 5%). In the one study that reported positive experiences only, a participant reported that she thought it was good “they are monitoring us all the time” [ 30 ]. Studies reporting negative experiences with monitoring had participants citing reasons such as feeling over-scrutinised [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…2 Included studies published over time relatively small number of high-income countries, with the top six countries for research on women's experiences of GDM healthcare being Australia (n = 11), Canada (n = 8), Sweden (n = 7), the United States (n = 6), the United Kingdom (n = 4) and China (n = 4). The remaining studies were spread across a number of countries, largely one study per setting: Austria [29], Brazil [30], Denmark [31], Ghana [32], India [33], Indonesia [34], Iran [35,36], Malaysia [37], New Zealand [38,39], Norway [40], Singapore [41], South Africa [42,43], Vietnam [44], Zimbabwe [45] (see Fig. 3).…”
Section: Research Settingsmentioning
confidence: 99%
“…Desta forma, a assistência ao pré-natal é de suma importância para que a gestante possa ter o acompanhamento e orientações durante a gestação para um desenvolvimento saudável tanto para mãe quanto para o feto. No Brasil, a assistência ao pré-natal, está garantido pela política de saúde o pré-natal na Atenção Primária pelo SUS, a qual deve ser oferecida e organizada de modo a estabelecer o atendimento das necessidades básicas das gestantes, com a finalidade de ter uma gestação tranquila e sem riscos, para que tenha um parto sem intercorrências, sem prejuízos à saúde da mãe e um recém-nascido (Nicolosi et al, 2019). Arze (2023) refere-se que, a falta de adesão de mulheres ao Pré-Natal, vem tendo um crescimento exponencial, tornando uma questão preocupante em casos de diabetes gestacional, polidramnia, hipertensão gestacional, sífilis e ocorrência de parto prematuro.…”
Section: Introductionunclassified
“…A relevância social dos estudos, apontam como principais respostas de mães grávidas a falta de adesão ao Pré-natal, inicia-se nos atendimentos de consulta sendo que, foi relatado as dificuldades de mães fazerem o pré-natal, devido residirem longe da unidade de saúde, a demora no atendimento às gestantes que dependem de insulina, o elevado números de consultas durante a mesma semana, o controle glicêmico rígido domiciliar e a precisão de reorganização familiar (Nicolosi et al, 2019).…”
Section: Introductionunclassified
“…Assim, rastrear esta patologia e manter os níveis glicêmicos da gestante adequados podem minimizar os riscos de complicações materno-fetais e pós-natais. Nicolosi et al (2019) apontam que também há riscos de hiperbilirrubinemia, hipocalemia, hipoglicemia e morbimortalidade do feto, além de incidência de aborto e malformações de primeiro trimestre (PEDRINI et al, 2020). Silva et al (2017) Esta classe de hipoglicemiantes orais está associada a menor ocorrência de prematuridade, partos cesáreos, redução de ganho de peso materno e de desfechos neonatais desfavoráveis como macrossomia, hipoglicemia, icterícia e internação em UTI neonatal.…”
unclassified